(untitled) (Deutscher Suchtkongress, 2023)
World drug matters affect different people in different ways. There is a large Global North and South disparity on accessibility of controlled medications for pain relief and care and they are communities on the global South that suffer most of the negative consequences of global drug production in terms of environmental degradation, violence, socio-economic development, and human rights. Stigma and fragile environments place certain sub-population groups more at risk than others. For example, men use drugs more than women, but globally women have a larger treatment gap; homeless people are particularly vulnerable to HIV outbreaks among people who inject drugs. While the health harm of drugs remains arguably contained when compared with alcohol and tobacco, there counties to be an increase in the number of people who use drug, those with drug use disorders and new data on people who inject drugs have made us to revisit the global number of PWID to a 18% higher level. Markets such as cocaine and synthetic drugs continue to show signs of expansion. While the health harm of drugs has been widely documented, the environmental impact of drugs has only recently started to be studied. Drugs are not the main factors that affect the global environmental agenda, but they have a significant impact on some local communities and at individual level. The drug supply chains have a large carbon footprint impact for quantity produced. Illegal drug cultivation destroys ecosystems and directly and indirectly trigger deforestation. The illegal drug economy opens up the territory in fragile ecosystems, such as the Amazon Basin, to organized criminal groups that exploit the territory through land-grabbing, illegal logging, illegal mining, trafficking in wildlife and other crimes that affect the environment. These drug trafficking organizations are not just exacerbating deforestation but are also accelerating convergent crime ranging from corruption, tax and financial crimes, to homicide, assault, sexual violence, exploitation of workers and minors, and the victimization of those defending the environment and Indigenous Peoples. Manufacture of synthetic drugs has also important implications for the soil, water, and air, as well as indirect effects on organisms, animals, and the food chain of local communities.